Miłosz: autorefleksja jako temat poetyckiego opisu - Stelmaszczyk, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Czesław Miłosz’s poetry displays two reverberating topics which may be defined as two contradictory existence and world experiences. One of those is admiration for the beauty of the world and awe consequent upon capturing the simultaneous existence of individual entities (Awe), whilst the other is the topic of lack of fulfilment, torment, the feeling of lack of authenticity, blame, and shame (This). Miłosz depicts his “I” (represented by various personae), split between individual consciousness, a strong sense of individuality, distinct from the commune of ordinary people (a strand salient in the pre-war volume Three Winters), as well as nurturing a feeling of strong bonds with the society. The poet’s self-reflection holds for both topics, while the autobiographic discourse is orientated to the questions about the functions of poetic language and about the status and sense of poetry, thereby addressing self-topicality.